NANOTECHNOLOGY IN CANCER DRUG DELIVERY: INNOVATIONS AND CLINICAL APPLICATIONS - Dr Aishwarya Alavandar; Dr. Prathamesh V Pakale; Dr. M.A.Q. Ansari; Dr. Mukti Sharma; Dr. Santhosha Kulal (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background and Objective: Traditional therapies are poorly specific and cause severe side effects and reduced efficacy in cancer treatment. Engineered nanocarriers for drug delivery are promising solutions provided by nanotechnology that can enhance the precision of drug delivery, reduce toxicity, and improve therapeutic outcomes. In this review, recent advances and clinical applications of nanotechnology for cancer drug delivery are explored.Materials and Methods: Databases like PubMed, Scopus, and Web of Science were used for a systematic review of the literature. Studies published from 2014-2024 were included based on the criteria of nanocarriers' design, targeting strategies, and clinical evaluations. Preclinical, in vitro, and clinical studies were assessed for quality using standardized tools like the Cochrane Risk of Bias Tool and ARRIVE guidelines. Statistical analysis, performed using one-way ANOVA, validated significant findings with p-values